Using a technology acceptance model to determine factors influencing continued usage of mobile money service transactions in Ghana - Afful Ekow Kelly; Sellappan Palaniappan (Journal of Innovation and Entrepreneurship, 2023)
Investigating and exploring factors influencing the continued usage and acceptance of mobile money transaction services in Ghana. The study employed the Technology Acceptance Model (TAM) with 406 mobile money users from Ghana's Savannah and Bono regions. According to the study, perceived risk perceived cost, social influence, perceived usefulness and ease of use had repercussions on users' attitudes which influenced users' final decision to continue to use mobile money services in Ghana. The social influence positively impacted users through social networking in pushing the adoption and continued usage of mobile money services in the study area. However, the construct of Perceived trust had a positive impact on users' decisions resulting in their negative attitude to mobile money services.
Keywords: 650; Mobile banking; Adoption; Continuous usage; Digital money; Mobile money